2017
DOI: 10.3390/ijms18030596
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Embryo as an In Vivo Model for Behavioral and Pharmacological Characterization of Methylxanthine Drugs

Abstract: Zebrafish embryo is emerging as an important tool for behavior analysis as well as toxicity testing. In this study, we compared the effect of nine different methylxanthine drugs using zebrafish embryo as a model. We performed behavioral analysis, biochemical assay and Fish Embryo Toxicity (FET) test in zebrafish embryos after treatment with methylxanthines. Each drug appeared to behave in different ways and showed a distinct pattern of results. Embryos treated with seven out of nine methylxanthines exhibited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…These results are consistent with a previous study that demonstrated blood flow velocity reduction in zebrafish after MS222 treatment [14]. The second compound used is IBMX, one of the methylxanthines having coupled heterocyclic organic compounds consisting of pyrimidinedione and imidazole rings [10]. This compound reportedly has two major toxicities, cardiac toxicity and hemodynamic perturbations [9].…”
Section: Functional Assessment Of Cardiovascular Performance In Zebrasupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with a previous study that demonstrated blood flow velocity reduction in zebrafish after MS222 treatment [14]. The second compound used is IBMX, one of the methylxanthines having coupled heterocyclic organic compounds consisting of pyrimidinedione and imidazole rings [10]. This compound reportedly has two major toxicities, cardiac toxicity and hemodynamic perturbations [9].…”
Section: Functional Assessment Of Cardiovascular Performance In Zebrasupporting
confidence: 89%
“…On the other hand, 3-isobutyl-1-methylxanthine (IBMX), one of the most toxic methylxanthines, has been reported to have potent cardiac toxicity and cause severe hemodynamic perturbations [9]. It was also found to have epileptogenic effects in animal studies, although in human studies, an indication of epilepsy was not found [10]. In addition to heart rate, the effect of drug treatments on other cardiovascular function parameters, such as blood flow velocity, stroke volume, and cardiac output remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to have an excellent correlation with the Acute Toxicity Test in adults [ 67 ], and has been proposed to be a worthy range-finder prior to more extensive testing [ 68 ]. A recent study used the FET test to evaluate toxicity of methylxanthine drugs, which revealed a strong positive correlation between TC50 measurements of mortality, morphological defects and teratogenicity in zebrafish embryos and published mammalian LD50 values [ 69 ].…”
Section: Approaches For Measuring Nanoparticle Toxicity In Zebrafimentioning
confidence: 99%
“…Published by Rynnye Lyan Resources were exposed in duplicates to either a control or different concentrations of jackfruit seed crude extracts. Exposure was static, which means that the sample test solutions were not renewed throughout the experimental period to guarantee minimum manipulation of the embryos (Guarienti et al, 2014;Basnet et al, 2017). Twelve embryos were used for each concentration, so a total of 84 embryos for each replicate were analyzed.…”
Section: Collection and Exposure Of Zebrafish Embryosmentioning
confidence: 99%